Formação de educadores do campo: o Curso de Licenciatura em Educação do Campo da Universidade Estadual do Ceará - Oliveira, Diana Nara da Silva (2023)
The research reflected on the training of field educators from a dialectical analysis on the contributions of this training to build a new profile of educator/field, starting point the implementation of the Degree Course in Field Education of the Faculty of Philosophy Dom Aureliano Matos, campus of the State University of Ceará. In methodological terms, the research is based on the Dialectical Historical Materialism-MHD, being the most appropriate approach to understand the objective reality arranged in the Degree in Field Education, qualitative and structured research on fundamental procedures, merging techniques of Bibliographical, Documentary and Field Research. In the bibliographical research was carried out a survey of academic works in the state of Ceará and in the national territory on the most recent productions that support the theoretical framework regarding the Field Degree, training of teachers of the field, Social Movements and educational policy of the field, seeking to understand the process of creation of LEDOCs in Brazil, as well as in the state of Ceará, in addition to understanding the participation of social movements in the construction of this policy. The study was based on the documentary source, where a survey of the documents regarding the creation of the policy of training of teachers of the field in the country, as well as on the implementation of LEDOC in the UECE, in addition to documents related to funding, pedagogical part and permanence of students along the student path. The field research based on interviews sought to understand the operationalization of the educational policy of training of teachers in the field in UECE from interviews with graduates, course coordination and representative of the education sector of the MST. As a result, we built a bibliographic collection on the subject in question, we conclude that the insertion of this course in the set of FAFIDAM degrees allowed a change of posture in the academic community, especially in the way they see the MST and the social struggles We found significant impacts for the State University of Ceará, the FAFIDAM campus and students. We also evaluated the repercussions of the National Movement of Rural Education in the state of Ceará.